A Track Record on SHOX: From Basic Research to Complex Models and Therapy - Marchini, Antonio; Ogata, Tsutomu; Rappold, Gudrun A. (Endocrine reviews, 2016)
SHOX deficiency is the most frequent genetic growth disorder associated with isolated and syndromic forms of short stature. Caused by mutations in the homeobox gene SHOX, its varied clinical manifestations include isolated short stature, Léri-Weill dyschondrosteosis, and Langer mesomelic dysplasia. In addition, SHOX deficiency contributes to the skeletal features in Turner syndrome. Causative SHOX mutations have allowed downstream pathology to be linked to defined molecular lesions. Expression levels of SHOX are tightly regulated, and almost half of the pathogenic mutations have affected enhancers. Clinical severity of SHOX deficiency varies between genders and ranges from normal stature to profound mesomelic skeletal dysplasia. Treatment options for children with SHOX deficiency are available. Two decades of research support the concept of SHOX as a transcription factor that integrates diverse aspects of bone development, growth plate biology, and apoptosis. Due to its absence in mouse, the animal models of choice have become chicken and zebrafish. These models, therefore, together with micromass cultures and primary cell lines, have been used to address SHOX function. Pathway and network analyses have identified interactors, target genes, and regulators. Here, we summarize recent data and give insight into the critical molecular and cellular functions of SHOX in the etiopathogenesis of short stature and limb development.